2021
DOI: 10.1042/bsr20203559
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic values of microRNA-196a in cancer

Abstract: MicroRNA-196a (miR-196a) was previously reported to be up-regulated in cancers, and it has the diagnostic and prognostic values in cancers. Whereas, the conclusion was still unclear according to the published data. To assess such roles of miR-196a in cancers, the present study was conducted based on published data and online cancer-related databases. To identify the relevant published data, we searched articles in databases and then the relevant data were extracted to evaluate the correlation between miR-196a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
4
7
0
1
Order By: Relevance
“…Apart from this, we also discover that the average Cy3 emission of A549 cells is ∼1.4-fold higher than that of the HeLa cells. The recovery in different types of cancer cells is likely ascribed to the high-abundance nature of miRNA-196a in lung tissue-related tumors, and such a content trend agrees well with the reverse transcription-polymerase chain reaction (RT-PCR) data (Figure S20). Furthermore, the imaging accuracies are confirmed by the flow cytometry analysis (Figure S19B), among which faultless consistence between these different detection means is presented.…”
Section: Results and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Apart from this, we also discover that the average Cy3 emission of A549 cells is ∼1.4-fold higher than that of the HeLa cells. The recovery in different types of cancer cells is likely ascribed to the high-abundance nature of miRNA-196a in lung tissue-related tumors, and such a content trend agrees well with the reverse transcription-polymerase chain reaction (RT-PCR) data (Figure S20). Furthermore, the imaging accuracies are confirmed by the flow cytometry analysis (Figure S19B), among which faultless consistence between these different detection means is presented.…”
Section: Results and Discussionsupporting
confidence: 81%
“…In light of the potential role of miRNA-196a in the development of lung tumors, establishing an assay method with favorable sensitivity and specificity to precisely measure the intracellular levels at various physiological states can provide meaningful information for clinical diagnosis. 40 To this end, the A549 cells are treated with two forms of frequently used biochemical regulation reagents (250 nM miRNA mimic and 250 nM inhibitor), and the sensing of intracellular targets is further accomplished. As shown in Figure S21A, in comparison with the control cells (without any treatments, middle images), a dramatic signal enhancement is detected in the up-regulation group (top images), while the fluorescence intensity appears as a certain decline phenomenon for the down-regulating manner (bottom images).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pooled analysis revealed that elevated miR-196a levels in tumor tissues (HR = 2.54, 95% CI: 1.79–3.61, P Heterogeneity = 0.000, I 2 = 75.8%) or serum and plasma (HR = 4.06, 95% CI: 2.67–6.18, P Heterogeneity = 0.668, I 2 = 0%) correlated with unfavorable survival. In conclusion, tumor tissue or blood-derived miR-196a could be used a prognostic and diagnostic biomarker for cancers such as BC [ 77 ]. Another meta-analysis reported that miR-206 plays an important role in cancers and it could be used as a prognostic biomarker.…”
Section: Clinical Value Of Non-coding Rnas In Bcmentioning
confidence: 99%
“…Results have been inconclusive on other micro-RNAs [123,131]. Deregulated expression of several micro-RNAs was not only associated with ACC diagnosis but also with prognosis [114,124,132,133]. The diagnostic accuracy of micro-RNAs is shown to be variable [134].…”
Section: Mirnaomementioning
confidence: 99%